The practice of employee empowerment: a case study of total quality management in Bilateral Division in Ministry Of International Trade And Industry (MITI) / Irena Sha’aban - Sha’aban, Irena (Faculty of Business and Management, 2009)
This study provides an analysis regarding employees’ empowerment as one of the elements in Total Quality Management. The purpose of this study is to review the effectiveness of TQM implementation by the case of Bilateral Division in Ministry of International Trade and Industry (MITI). The case is expected to reveal the level of TQM implementation in the service sector, to be specific in MITI itself. The purpose of study, background of the study and issues are deeply elaborated in detail under chapter of Introduction as well as literature review which under the Second Chapter. In order to analyze the issues, the data collected from the primary and secondary sources. Data and information is collected from the articles, internet and journal as well as interviewing staffs and employees from Bilateral Division. Last but not least, the case will highlight certain recommendations which should be noted by MITI for the future benefit.